Risks to Early Childhood Health and Development in the Postconflict Transition of Northern Uganda - Theresa A. McElroy; Stella Atim; Charles P. Larson; Robert W. Armstrong (International Journal of Pediatrics)
Research from numerous fields of science has documented the critical importance of nurturing environments in shaping young children's future health and development. We studied the environments of early childhood (birth to 3 years) during postconflict, postdisplacement transition in northern Uganda. The aim was to better understand perceived needs and risks in order to recommend targeted policy and interventions. Methods. Applied ethnography (interview, focus group discussion, case study, observational methods, document review) in 3 sites over 1 year. Results. Transition was a prolonged and deeply challenging phase for families. Young children were exposed to a myriad of risk factors. Participants recognized risks as potential barriers to positive long-term life outcomes for children and society but circumstances generally rendered them unable to make substantive changes. Conclusions. Support structures were inadequate to protect the health and development of children during the transitional period placing infants and young children at risk. Specific policy and practice guidelines are required that focus on protecting hard-to-reach, vulnerable, children during what can be prolonged and extremely difficult periods of transition.